SIZE DISTRIBUTION AND MATURITY OF THE SLIMEHEADS (Hoplostethus crassispinus) lN THE DEEP SEA AROUND SIMEULEU ISLAND, WESTERN SUMATERA, EASTERN INDIAN OCEAN - Badrudin Badrudin; Ali Suman; Awwaludin Awwaludin (Research Center for Fisheries, 2007)
The slimeheads (Hoplosfefhus spp.) provide one of the likely economic important deep sea demersal fish resources in the near future. The fish was caught in western part of Sumatera, in the depth of more than 500 m deep, and was found in substantial amount in the deep waters around Simeuleu lsland and the western off Banda Aceh. Data analysis was limited to the biological aspects, including length relationship, and maturity.